The Importance of Olfaction for Mixed Paternity in Birds - Charlotta Kvarnemo; Alice Anderstedt; Maria Strandh; Donald Blomqvist (Ecology and Evolution)
ABSTRACT Olfaction can aid individuals in finding genetically compatible mates in many animals, while high levels of mixed paternity may result from a limited ability to evaluate their mate's genetic profile against their own before mating. To test this suggestion and explore if olfaction may indeed influence mating patterns in birds, we combined published measures of olfactory ability with data on genetic mating pattern in the same species, across a phylogenetically broad range of species. We used three measures of olfaction: (1) olfactory bulb diameter, (2) olfactory bulb volume and (3) number of olfactory receptor genes (148, 134 and 48 species, respectively). These measures were then matched to species‐specific estimates of mating pattern, measured as percentage of broods with mixed paternity (> 1 male siring offspring in the same brood). Limited overlaps between the datasets resulted in 30 matched species for olfactory bulb diameter, 31 for olfactory bulb volume and 15 for olfactory receptor genes. Controlling for brain size (telencephalon), we then correlated olfaction to mating pattern, and found that the bigger the relative olfactory bulb diameter, the lower the proportion of mixed paternity. In contrast, there was no significant correlation between olfactory bulb volume or number of receptor genes and paternity. This study thus indicates that mating patterns in birds may be influenced by olfactory ability, measured as olfactory bulb diameter. Next, we suggest expanding the datasets by collecting olfactory‐focused measures, targeting species for which paternity measures already exist, to allow a full phylogenetic analysis.